Antagonistic and plant growth promoting Bacillus sp. MBRL 576 enhances the growth and yield of rice (Oryza sativa L.) - Tamreihao, K; Nimaichand, Salam; Ningthoujam, Debananda S (ORYZA-An International Journal of Rice, 2018)
A Bacillus sp. strain MBRL 576 isolated from rice rhizosphere was tested for antagonism against six rice fungal pathogens, and further evaluated for plant growth promotion in rice under in vitro condition. The results indicated that the Bacillus sp. MBRL 576 showed antagonistic activity against all the tested fungal pathogens by producing diffusible and volatile compound(s) and fungal cell wall degrading enzymes such as ï¢-1,3- glucanase, ï¢-1,4-glucanase, lipase and protease. Besides antagonism, this strain also produced 10 Âµg/ml of IAA, solubilize inorganic phosphate up to 88 Âµg/ml, catecholate type of siderophore and ACC deaminase. Rice seeds treated with Bacillus sp. strain MBRL 576 significantly increased the growth and grain yield under net house condition and even under pathogen challenged conditions. Overall, this strain could be used as potential bioinoculant to enhance growth promotion of agricultural crops including rice.